Introduction of Groundwater Filtration Technology for Drinking Water in Coastal Communities in Muara Gembong - Himawan Hadi Sutrisno; Pratomo Setyadi; Jafar Amiruddin; Catur Setyawan K; Triyono; Fransisca Maria Farida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This Community Service activity aims to introduce groundwater filtration technology to produce potable water in the coastal area of Muara Gembong Beach, Bekasi. The groundwater filtration uses a membrane filtration method combined with ultraviolet (UV) light to achieve ideal and drinkable water conditions for the community. The membrane filtration method serves to filter dissolved particles in the water that are microscopic and under low pressure. Meanwhile, the use of ultraviolet light functions to kill microorganisms that may not be filtered by the membrane. The combination of these two groundwater filtration methods produces drinking water sourced from wells around the Muara Gembong Beach area in Bekasi. Key words: drinking water, estuary gembong, training for the community Abstrak Kegiatan Pengabdian kepada Masyarakat ini bertujuan memperkenalkan teknologi penyaringan air tanah untuk menjadi air siap minum pada daerah pesisir Pantai Muara Gembong Bekasi. Penyaringan air tanah menggunakan metode filtrasi membrane dan dikombinasikan dengan penggunaan Sinar Ultraviolet untuk mendapatkan kondisi air yang ideal dan siap minum untuk masyarakat. Metode filtrasi membrane berfungsi sebagai penyaring partikel yang terlarut pada komposisi air yang bersifat mikro dan bertekanan rendah. Sedangkan pemanfaatan sinar Ultra violet berfungsi mematikan mikro organisme yang memungkin tidak tersaring dalam filtrasi membrane. Kombinasi 2 metode penyaringan air tanah ini menghasilkan air minum yang berasal dari sumur tanah di sekitar Kawasan Pantai Muara Gembong Bekasi Kata kunci: air minum, muara gembong, pelatihan kepada masyarakat